2021
DOI: 10.1007/978-981-16-5063-5_26
|View full text |Cite
|
Sign up to set email alerts
|

Total Quality Management and Social Responsibility an Approach Through Their Synergies in Higher Education Institutions

Abstract: Growing social concerns have led organisations to think evolutionarily about quality as it is not only relevant to satisfy customers, generate quality products or services and focus on results but also to encourage a participatory, flexible and sustainable value-oriented management. Due to the complex environment and structure of higher education, quality measurement and management have created a number of challenges. Around the world, higher education institutions have adopted various quality management pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Third, with a path coefficient of 0.0.989 and a qualitative correlation coefficient of 0.390094, the influence of TQM on the quality of community service was assessed to be significant at 0.01. These findings are consistent with those of previous studies (Nogueiro et al, 2011(Nogueiro et al, , 2017(Nogueiro et al, , 2022Khoja et al, 2017;Banerjea, 2018;Yeung, 2018;Castillo, 2020), while these results differ from Koch (2003) which confirmed that the effect is small and identified the reasons for this.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Third, with a path coefficient of 0.0.989 and a qualitative correlation coefficient of 0.390094, the influence of TQM on the quality of community service was assessed to be significant at 0.01. These findings are consistent with those of previous studies (Nogueiro et al, 2011(Nogueiro et al, , 2017(Nogueiro et al, , 2022Khoja et al, 2017;Banerjea, 2018;Yeung, 2018;Castillo, 2020), while these results differ from Koch (2003) which confirmed that the effect is small and identified the reasons for this.…”
Section: Discussionsupporting
confidence: 93%
“… Castillo (2020) reaffirmed the necessity to develop and implement TQM concepts to all aspects of higher education academic units, including teaching, research, community services, and administrative support. Furthermore, Nogueira emphasized in his different studies that TQM and CSR are two increasingly significant dimensions in creating a sustainable and hopeful future for all stakeholders, and that they are important dimensions in achieving a sustainable and promising future for all stakeholders (among others, students and workers employers, and society in general; Nogueiro et al, 2011 , 2017 , 2022 ). In Algerian universities, Khelifa et al (2013) and Keffane et al (2020) emphasized the existence of numerous effects of total quality management, including improving the quality of community service.…”
Section: Introductionmentioning
confidence: 99%
“…Among the critical components of TQM, HRM contributes to CSR (Khurshid et al, 2021). However, the relationship between the two variables was insignificant (Nogueiro et al, 2022). Studying the relationship between TQM practices and CSR in Spanish organizations using the European Foundation for Quality Management model, the researchers found no significant relationship, except in process management (Ershadi et al, 2019).…”
Section: Tqm Csr and Green Innovationmentioning
confidence: 98%
“…However, these studies presented TQM and CSR as separated constructs while there are some theoretical calls for integrated framework of these principles. According to Nogueiro, Saraiva (6) illuminating how TQM principles can enhance CSR initiatives, thereby improving organizational performance. In addition, Tsou, Huang (7) suggested that the integration of TQM and CSR leads to improved firm performance, setting a future research agenda to understand this interplay more deeply.…”
Section: Introductionmentioning
confidence: 99%